Translational research in pituitary tumours - Stalla, Günter K (2019)
Although effective treatment regimens (surgical resection, drug treatment with dopamine agonists or somatostatin analogues, radiotherapy) have been established for the therapy of most pituitary tumours, a considerable proportion of affected patients cannot completely cured due to incomplete resection or drug resistance. Moreover, even if hormone levels have been normalized, patients with hormone-secreting tumours still show persistent pathophysiological alterations in metabolic, cardiovascular or neuropsychiatric parameters and have an impaired quality of life. In this review reasons for the discrepancy between biochemical cure and incomplete recovery from tumour-associated comorbidities are discussed and the clinical management is delineated exemplarily for patients with acromegaly and Cushing's disease. In view of the development of additional treatment concepts for the treatment of pituitary adenomas we speculate about the relevance of RSUME as a potential target for the development of an anti-angiogenic therapy. Moreover, the role of BMP-4 which stimulates prolactinoma development through the Smad signalling cascade is described and its role as putative drug target for the treatment of prolactinomas is discussed. Regarding the well-known resistance of a part of somatotropinomas to somatostatin analogue treatment, recently identified mechanisms responsible for the drug resistance are summarized and ways to overcome them in future treatment concepts are presented. Concerning novel therapeutic options for patients with Cushing's disease the impact of retinoic acid, which is currently tested in clinical studies, is shown, and the action and putative therapeutic impact of silibinin to resolve glucocorticoid resistance in these patients is critically discussed.